Developing an Irreversible Inhibitor of Human DDAH‐1, an Enzyme Upregulated in Melanoma. Issue 4 (26th February 2014) - Wang, Yun; Hu, Shougang; Gabisi, Abdul M.; Er, Joyce A. V.; Pope, Arthur; Burstein, Gayle; Schardon, Christopher L.; Cardounel, Arturo J.; Ekmekcioglu, Suhendan; Fast, Walter
Abstract Inhibitors of the human enzyme dimethylarginine dimethylaminohydrolase‐1 (DDAH‐1) can raise endogenous levels of asymmetric dimethylarginine (ADMA) and lead to a subsequent inhibition of nitric oxide synthesis. In this study, N5‐(1‐imino‐2‐chloroethyl)‐L‐ornithine (Cl‐NIO) is shown to be a potent time‐ and concentration‐dependent inhibitor of purified human DDAH‐1 (KI=1.3±0.6 μM; kinact=0.34±0.07 min−1), with >500‐fold selectivity against two arginine‐handling enzymes in the same pathway. An activity probe is used to measure the "in cell" IC50 value (6.6±0.2 μM) for Cl‐NIO inhibition of DDAH‐1 artificially expressed within cultured HEK293T cells. A screen of diverse melanoma cell lines reveals that a striking 50/64 (78 %) of melanoma lines tested showed increased levels of DDAH‐1 relative to normal melanocyte control lines. Treatment of the melanoma A375 cell line with Cl‐NIO shows a subsequent decrease in cellular nitric oxide production. Cl‐NIO is a promising tool for the study of methylarginine‐mediated nitric oxide control and a potential therapeutic lead compound for other indications with elevated nitric oxide production, such as septic shock and idiopathic pulmonary fibrosis.